Desenvolvimento de forrageiras tropicais submetidas a diferentes tensões de água no solo - Gonçalves, Morgana Scaramussa (2016)
Brazil is going through a severe water insecurity, lack of water, combined with, lack of rain, lack of planning and excessive consumption, which results in lack of water for personal consumption, maintenance of professional and agricultural activities. Th